Gambaran Kejadian Nyeri Tenggorok dan Serak pada Pasien yang Menjalani Anestesi Umum Endotrakeal di RSUD Arifin Achmad Pekanbaru - Fitri Fahriyani; Dino Irawan; Eka Bebasari (Jurnal Ilmu Kedokteran, 2014)
Sore throat and hoarseness are common complications after endotracheal intubation. The incidence of sore throat andhoarseness after endotracheal intubation varies from 14 to 75%. Although regarded as minor complications, sorethroat and hoarseness contribute to postoperative morbidity and patient dissatisfaction. The aim of this study were todetermine the incidence of sore throat and hoarseness after endotracheal general anesthesia and to describe associatedrisk factors at Arifin Achmad Public Hospital. This study used a descriptive cross sectional method. A total of 88patients who underwent endotracheal general anesthesia were enrolled in this study. Data of the patient such asgender, age, duration of intubation and endotracheal tube size were collected from medical record and direct observationat the time of operation. All of the patients were interviewed within 24-36 hours after surgery to collect data such assmoking history, sore throat complaint and hoarseness complaint. The evaluation of sore throat degree was accomplishedwith a Capan’s scale for sore throat and hoarseness degree was accomplished with a Stout’s scale for hoarseness. Theresult showed that 18 patients (20.4%) experienced sore throat and 34 patients (38.6%) experienced hoarseness aftersurgery.